The Effect of Firm Size, Profitability, Leverage, and Environmental Performance on Environmental Disclosure - Ali Riza Fahlevi; Aditya Novanto Nomba; Irsa Pramesti Rahmadani; Aleta S. P. Gumilar (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aims to explain the influence of firm size, profitability, leverage, and environmental performance on environmental disclosure. This research is a quantitative study with purposive sampling from the population of all listed firms in the SRI-KEHATI Index for 2017-2021. The final sample used in this research is 60 observations from 12 firms that have always published their sustainability reporting during the research period. A panel data regression approach was used to test the hypothesis. This research found that the firm size variable has a negative effect on environmental disclosure. However, the environmental performance variable has a positive effect on environmental disclosure. On the other hand, profitability and leverage variables do not affect environmental disclosure. Further researchers are suggested to add another independent variable that can significantly influence environmental disclosure. Besides that, future researchers are also expected to be able to add observational data used in the study to obtain more optimal results.